1998
DOI: 10.1038/sj.bjp.0701604
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of mercaptoethylguanidine, a selective inhibitor of inducible nitric oxide synthase, in ligature‐induced periodontitis in the rat

Abstract: 1 Excessive production of nitric oxide (NO), and the generation of peroxynitrite have been implicated in various proin¯ammatory conditions. In the present study, using mercaptoethylguanidine (MEG), a selective inhibitor of iNOS and a peroxynitrite scavenger, we investigated the role of iNOS and peroxynitrite in a rat model of periodontitis. 2 Periodontitis was produced in rat by a ligature of 2/0 braided silk placed around the cervix of the lower left 1st molar. Animals were then divided into two groups: one g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
176
1
15

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 49 publications
(72 reference statements)
10
176
1
15
Order By: Relevance
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionmentioning
confidence: 70%
“…NO has been implicated in the pathogenesis of apical infection [45], periapical granulomas [46], and inflamed human dental pulp [47]. Increased iNOS expression in gingiva was shown in periodontitis [20,22,26,28,31], ligature-induced periodontitis [27], experimental periodontitis [30,46], inflamed gingiva [23], localized aggressive periodontitis [21], and recently by our group in aggressive periodontitis (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since large amounts of NO are toxic, NO has been implicated in the pathophysiology of several inflammatory conditions [9][10][11][12] . In such diseases, under conditions of high and sustained NO production, reactive nitrogen oxide species (RNS) (such as nitrogen dioxide, NO 2 ; dinitrogen trioxide, N 2 O 3 ; and peroxynitrite, ONOO -) are formed by reactions with reactive oxygen species (ROS), and may result in nitrosative or oxidative stress [13,14] . Some experimental and clinical evidence indicates that pharmacological inhibition of iNOS triggers anti-inflammatory responses, which may be of clinical use [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental and clinical evidence indicates that pharmacological inhibition of iNOS triggers anti-inflammatory responses, which may be of clinical use [12,13] . Furthermore, since NO can interact with other inflammatory mediators, it may be part of a system of dual or multiple inhibitors of the inflammatory cascade [14] . Based on these assumptions, the aim of this study was to locally and systemically assess the effect of adjunctive SDD treatment on nitrosative stress in moderate to advanced chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%